Thermal and Photochemical Decomposition of Aqueous Bromamine-B - Mohana, K.N.; Yathirajan, H.S.; Ananda Murthy, A.S.; Lokanatha Rai, K.M. (Asian Journal of Chemistry, 2010)
Thermal decomposition of aqueous bromiamine-B is studied between the temperature range 50-90ºC. Photolysis of aqueous bromine-B is studied with a UV light source (λ = 2557 Å) and the products have been identified. A suitable photolytic mechanism is suggested based on the observed results.